Pelatihan Pengolahan dan Pemanfaatan Jahe Merah dan Kulit Buah Naga Menjadi Permen Jelly untuk Alternatif Pengobatan Penyakit Degeneratif di Desa Kalasey II Kabupaten Minahasa: Training on Processing and Utilization of Red Ginger and Dragon Fruit Peel into Jelly Candy for Alternative Degenerative Disease Treatment in Kalasey II Village, Minahasa Regency - Maramis, Rilyn Novita; Ulaen, Selfie Petronela Joice; Nahor, Evelina Maria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The utilization of natural materials as traditional medicine is considered to have less side effects than drugs derived from chemicals. Plants that can be utilized as traditional medicine are red ginger and dragon fruit skin. Red ginger is widely known as a cooking spice and is used in medicine because it contains compounds with broad biological activities and dragon fruit has properties as an antioxidant, but its skin has not been utilized and is only discarded as garbage or waste. Dragon fruit skin contains high antioxidant compounds that are beneficial for health and can be used as a natural coloring material. Jelly candy is one of the processed food products that is easy to make by utilizing the active substances of red ginger juice and dragon fruit skin juice with additional ingredients such as agar. The purpose of this activity is to train the community in processing jelly candy from red ginger juice and dragon fruit peel juice. The method of implementation is in the form of training on how to process red ginger juice and dragon fruit peel juice into jelly candy. After the training, it was found that the Community Service Activity through this training can increase the knowledge and skills of the community of Kalasey II Village, Mandolang District, Minahasa Regency about processing red ginger juice and dragon fruit peel juice into jelly candy which is beneficial for health.